Potential Consequences of Essential Drug Shortages in Canada: Brain Abscess due to Nocardia farcinica Associated with Dapsone Prophylaxis for Pneumocystis jirovecii Pneumonia - Terry C Wuerz; Eric J Bow; Matthew D Seftel (Canadian Journal of Infectious Diseases and Medical Microbiology)
In 2012, Canadian pharmacies experienced a shortage of trimethoprim-sulfamethoxazole tablets. Drug shortages may result in unintended clinical consequences such as infection with pathogens against which the alternative medication is ineffective. This is highlighted in the present article, which describes a case of brain abscess due to Nocardia species that developed while receiving dapsone as an alternative for prophylaxis against Pneumocystis jirovecii pneumonia in a highly immune-suppressed patient. Clinicians should be cognizant of these issues when prescribing alternative agents.